Management of adults with diabetes on the haemodialysis unit: summary of guidance from the Joint British Diabetes Societies and the Renal Association. Issue 8 (17th July 2018) - Frankel, A. H.; Kazempour‐Ardebili, S.; Bedi, R.; Chowdhury, T. A.; De, P.; El‐Sherbini, Nevine; Game, F.; Gray, S.; Hardy, D.; James, J.; Kong, M.‐F.; Ramlan, G.; et al.
Abstract: Diabetic nephropathy remains the principal cause of end‐stage renal failure in the UK and its prevalence is set to increase. People with diabetes and end‐stage renal failure on maintenance haemodialysis are highly vulnerable, with complex comorbidities, and are at high risk of adverse cardiovascular outcomes, the leading cause of mortality in this population. The management of people with diabetes receiving maintenance haemodialysis is shared between diabetes and renal specialist teams and the primary care team, with input from additional healthcare professionals providing foot care, dietary support and other aspects of multidisciplinary care. In this setting, one specialty may assume that key aspects of care are being provided elsewhere, which can lead to important components of care being overlooked. People with diabetes and end‐stage renal failure require improved delivery of care to overcome organizational difficulties and barriers to communication between healthcare teams. No comprehensive guidance on the management of this population has previously been produced. These national guidelines, the first in this area, bring together in one document the disparate needs of people with diabetes on maintenance haemodialysis. The guidelines are based on the best available evidence, or on expert opinion where there is no clear evidence to inform practice. We aim to provide clear advice to clinicians caring for this vulnerable population and to encourage and improve education for clinicians and people with diabetes to promote empowerment and self‐management. What's new?: Diabetic nephropathy remains the principal cause of end‐stage renal failure in high‐income countries 1 2 . People with diabetes on regular hospital haemodialysis are a vulnerable group at high risk of adverse cardiovascular outcomes 3 . These national guidelines, the first in this area, are intended to support the practice of all healthcare professionals who care for this vulnerable group of people. An abridged version of the guidelines is presented here and the full guidelines are available online at: www.diabetes.org.uk/joint-british-diabetes-society or https://abcd.care/joint-british-diabetes-societies-jbds-inpatient-care-group and should be consulted before designing a therapeutic intervention. These guidelines have been published previously in the British Journal of Diabetes and are reproduced here with permission of the publishers [ Br J Diabetes 2016; 16: doi.org/10.15277/bjd.2016.073] 4 .